2021
DOI: 10.1016/j.isci.2020.102021
|View full text |Cite
|
Sign up to set email alerts
|

A multi-pronged approach targeting SARS-CoV-2 proteins using ultra-large virtual screening

Abstract: SARS-CoV-2 related proteins were targeted in ultra-large in silico screens. Multiple functional sites on individual target proteins were screened. 17 virus-related targets, 45 screens, and 50 billion docking instances were covered. Conservation in some target sites means hits could exhibit pancoronavirus function. Screening results are available as an interactive web resource and for download.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 226 publications
2
68
0
Order By: Relevance
“…Computational protocols for HTVS vary widely across existing SARS-CoV-2 M pro screens, from accurate but expensive simulations for MMGBSA/PBSA scoring to standard docking. Gorgulla et al 18 screened Enamine Real, a billion-scale combinatorial product library, against various SARS-CoV-2 targets using QuickVina W—a slightly less accurate but computationally efficient flavor of AutoDock Vina. 64 Acharya et al 13 also screened Enamine Real with Autodock-GPU.…”
Section: Discussionmentioning
confidence: 99%
“…Computational protocols for HTVS vary widely across existing SARS-CoV-2 M pro screens, from accurate but expensive simulations for MMGBSA/PBSA scoring to standard docking. Gorgulla et al 18 screened Enamine Real, a billion-scale combinatorial product library, against various SARS-CoV-2 targets using QuickVina W—a slightly less accurate but computationally efficient flavor of AutoDock Vina. 64 Acharya et al 13 also screened Enamine Real with Autodock-GPU.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive research supports the relevance of CBR-PPAR dual targeting in the context of a broad range of pathologies. In fact, multitarget drugs can offer an improved therapeutic profile in complex diseases, as already occurs in multifactorial disorders such as cancer, neurodegenerative diseases, or psychiatric disorders [229]. In this sense, CB 2 R and PPARγ modulators are at the forefront of multitarget cannabinoid-related drugs.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…De novo M pro inhibitors have been identified by either in silico or physical screens. Three in silico screening studies are particularly relevant here: two studies that ranked more than one billion compounds each, but did not validate the identified hits 24 , 25 , and a third study that ranked 6.5 million compounds and validated seven top compounds, of which the most potent exhibited an IC50 of 4.2 μM in vitro 26 . Among the studies that employed physical screens to identify M pro inhibitors, one study screened a small library of chemical fragments for binding to M pro by X-ray crystallography and identified several hits, which, however, were not developed further 27 .…”
Section: Introductionmentioning
confidence: 99%